PEMENUHAN GURU PENDIDIKAN AGAMA SMP DI KOTA JAMBI - Abdul Aziz al-Bone (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2008)
AbstractThis study aimed at to find out the information dealing with the job fulfillment for religious teachers at the piblic and private junior high schools in Jambi City. Based on the findings, it can be concluded that (1) there are 155 religious education teachers in Jambi where 99 persons (63,87%) are civil servants and 55 persons (35,48%) are non-civil servants (honorarium), (2) most of the teachers are sarjana S-1 graduates (equivalent with Bachelor of Art); (3) they are mot evenly distributed, (4) the problem found in the case of remuneration of the religious education teachers is that the number of teachers hired by the government is much lower than the needs itself; (5) the teacher candidates are required to be S1 graduates is relevant to study program, have good personality, loyality, and physically and mentally, and have commitment to improve their personality.